(untitled) - Clouse, Barbara Fine (Boston, 2008)
Written with the kind of supportive tone found in a writing workshop, this three-in-one rhetoric/reader/handbook puts students in control of developing their own writing processes by teaching them how to become astute critics and editors of their work. Now in full-color, the seventh edition of The Student Writer offers new chapters on research, enhanced coverage of visual rhetoric including a new appendix on document design, new and enhanced coverage of plagiarism, and more.
Keywords: English language,Tiếng Anh; Rhetoric,Tu từ học